Pain and its Perceived Relatedness to the Onset, Maintenance, and Relapse of Opioid use Disorder: A Descriptive Study of Non-Treatment-Seeking Individuals - Johnathan Rausch; Parker Entrup; Megan Deaner; Jasmine King; O. Trent Hall (Canadian Journal of Pain)
Background Previous research has found chronic pain to be prevalent among individuals with opioid use disorder (OUD). The perception that pain is related to OUD onset, maintenance, relapse, and treatment delay has been noted in this population. However, prior works primarily involved treatment-engaged populations. Scant research describes such perceptions among non-treatment-seeking individuals.Aims This study describes pain burden and perceptions regarding the role of pain in OUD onset, maintenance, relapse, and addiction treatment delay in a sample of individuals with untreated OUD.Methods This cross-sectional study surveyed syringe exchange participants (n = 141). Participants responded to a survey including Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition OUD criteria, pain survey scales, demographic characteristics, and questions regarding pain and its perceived relatedness to aspects of OUD.Results Most participants reported pain within the past 4 weeks (127, 91.4%). Data displayed a skew toward more intense pain ratings, with 120 reporting their pain as greater than mild (86.3%). A majority of participants agreed that pain was responsible for their OUD onset (79, 56.4%), maintenance (76, 54.3%), past relapse experience (82, 57.9%), and treatment delay (81, 57.9%). Correlative analyses revealed that pain severity and interference measures displayed moderate and statistically significant associations with extent of perceived relatedness of pain to these aspects of OUD.Conclusions Among this sample of individuals with untreated OUD, pain and pain interference were prevalent. Pain was perceived to be related to OUD onset, maintenance, relapse, and treatment delay by a majority of the sample. These findings are in accordance with and expand upon prior works.Abbreviations OUD: opioid use disorder; DSM-5: Diagnostic and Statistical Manual 5; BPI: Brief Pain Inventory; NIDA: National Institute on Drug Abuse; IASP: International Association for the Study of Pain; MOUD: Medications for Opioid Use Disorder; IQR: Interquartile Range.